The Combination Effect of Applying Liming Levels and Bat Dung on Increasing Soil pH in Ultisol Soil - Charles Silahooy (International Journal of Educational Research Excellence (IJERE), 2024)
Providing organic matter can increase soil pH and increase soil fertility. Through liming plus organic fertilizer such as bat droppings, it is hoped that it can increase the soil pH. This research aims to study the combined effect of applying lime and bat droppings on increasing soil pH in ultisol soil. This research was carried out in a plastic house in Ouw Village, Central Maluku Regency, from August 2023 to January 2024. Analysis of soil properties was carried out at the Soil Laboratory, Faculty of Agriculture, Pattimura University. The experimental design used in this research was a Randomized Step Design (CRD) with a 4 x 4 x 4 factorial pattern, where the parameter studied was soil pH in ultisol soil. The results of the research showed that the application of liming levels and bat droppings had an effect on increasing soil pH in ultisol soil.